Circular RNA TLK1 Promotes Sepsis-Associated Acute Kidney Injury by Regulating Inflammation and Oxidative Stress Through miR-106a-5p/HMGB1 Axis - Xu, Hai-Ping; Ma, Xiao-Ying; Yang, Chen (Frontiers in Molecular Biosciences, 2021)
Sepsis is an inflammatory disorder and leads to severe acute kidney injury (AKI). Circular RNAs (circRNAs) have been identified as a critical type of regulatory non-coding RNA (ncRNAs) that present the important functions in various diseases. In this study, we identified a novel circRNA circTLK1 in the regulation of sepsis-induced AKI. We observed that the circTLK1 expression was elevated in the caecal ligation and puncture (CLP) rat model compared with the control rats. The urine levels of neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (Kim-1) and the serum levels of creatinine (sCr) and blood urea nitrogen (BUN) were increased by the CLP treatment in the rats but was blocked by the circTLK1 shRNA. The circTLK1 shRNA reduced the CLP-induced kidney injury in the rats. The circTLK1 knockdown repressed oxidation stress, inflammation, and apoptosis in sepsis-related AKI rat model. Moreover, the lipopolysaccharide (LPS) treatment increased the production of TNF-α, IL-1β, and IL-6 in the HK-2 cells, while the circTLK1 shRNA could attenuate the enhancement in the cells. The Bax and cleaved caspase3 expression was up-regulated but the Bcl-2 expression was down-regulated by the LPS in the HK-2 cells, in which circTLK1 depletion reversed this effect in the cells. The depletion of circTLK1 attenuated the LPS-induced apoptosis in the HK-2 cells. CircTLK1 enhanced HMGB1 expression by sponging miR-106a-5p in the HK-2 cells and miR-106a-5p and HMGB1 were involved in circTLK1-meidated injury of LPS-treated cells. Therefore, we concluded that circTLK1 contributed to sepsis-associated AKI by regulating inflammation and oxidative stress through miR-106a-5p/HMGB1 axis. CircTLK1 and miR-106a-5p may be employed as the potential targets for the treatment of AKI.